Technical aspects of the paintings at Britsum (Bulletin KNOB, 2000)
On a coat of plastering containing large pieces of broken shells a thick coat of lime was also applied with a brush. Construction lines were scratched in this not quite solidified preparatory coat here and there, probably with a wooden peg, and sometimes lines of charcoal are also visible. The colour blue is absent in the mural paintings, but it is present in the Madonna painting on the vault of the nave. Seventeen samples were taken to analyze the composition of layers and the pigments.A range of earth paints were found, but also the synthetic inorganic pigment yellow massicot, which was made by heating white lead. All these pigments belong to the classical palette and were executed in a secco technique probably with a binder containing protein.